Variables Associated with a Urinary MicroRNAs Excretion Profile Indicative of Renal Fibrosis in Fabry Disease Patients. (24th June 2019) - Jaurretche, Sebastián; Perez, Germán; Antongiovanni, Norberto; Perretta, Fernando; Venera, Graciela
Abstract : Introduction . In advanced Fabry nephropathy stages, enzyme replacement theraphy (ERT) efficacy decreases, due to its impossibility to reverse renal fibrosis. Therefore, the finding of early kidney fibrosis biomarkers in affected patients is of interest. During renal fibrosis miR-21, miR-192 and miR-433 (fibrosis promotors) are activated by transforming growth factor- β (TGF- β ), and miR-29 and miR-200 family (fibrosis supressors) are inhibited by TGF- β . The aim of this study is to analyze the probability that Fabry disease (FD) patients with some clinical variables can present an urinary microRNAs excretion profile indicative of renal fibrosis through a logistic regression analysis. Results . A population of 34 participants was included: 24 FD patients and 10 controls. 16/24 (66.66%) FD patients presented microRNAs urinary excretion profile indicative of renal fibrosis. This profile was observed by decrease of fibrosis suppresors miR-29 and miR-200 and not by increase of fibrosis promotors miR-21, miR192, and miR-433. Hypohidrosis, angiokeratomas, neuropathic pain, hearing loss, cardiac involvement, male gender, reduced α GalA activity, and renin-angiotensin-aldosterone system inhibitors treatment are associated with the appearance of amicroRNAs urinary excretion profile indicative of renal fibrosis. A probable beneficial effect on urinary microRNAs excretion profile was observed in patients receiving ERT with agalsidase beta. The correlation between parameters of renal function with each family of microRNAs was studied. The only association with statistical significance was found between miR-21 and urine albumin-creatinine ratio (p =0.021). Conclusions . A probable microRNAs regulation not mediated by TGF- β should be considered or TGF- β has a different effect in FD than in other nephropathies on microRNAs regulation. Typical clinical manifestations of classic FD are associated with appearance of urinary microRNAs profile indicative of renal fibrosis. FD patients express renal fibrosis biomarkers in urine prior to onset of pathological albuminuria. A direct correlation between urinary miR-21 and degree of albuminuria was observed.